2020
DOI: 10.1016/j.ajog.2020.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 46 pregnant women with a severe acute respiratory syndrome coronavirus 2 infection in Washington State

Abstract: BACKGROUND: The impact of coronavirus disease 2019 on pregnant women is incompletely understood, but early data from case series suggest a variable course of illness from asymptomatic or mild disease to maternal death. It is unclear whether pregnant women manifest enhanced disease similar to influenza viral infection or whether specific risk factors might predispose to severe disease. OBJECTIVE: To describe maternal disease and obstetrical outcomes associated with coronavirus disease 2019 in pregnancy to rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
227
3
19

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(264 citation statements)
references
References 45 publications
15
227
3
19
Order By: Relevance
“…Overall, 487 (76.5%), 101 (15.9%), and 49 (7.7%) were diagnosed on admission as having, respectively, mild, severe, and critical COVID‐19 disease, according to clinical criteria defined by the Chinese Centre for Disease Control and Prevention 8 . Medical co‐morbidities were reported for 359 women 7,9–35 . The most common co‐morbidity was overweight or obesity (n=118, 32.9%), bronchial asthma (n=37, 10.3%), essential hypertension (n=21, 5.8%), and type 2 diabetes mellitus (n=10, 2.8%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 487 (76.5%), 101 (15.9%), and 49 (7.7%) were diagnosed on admission as having, respectively, mild, severe, and critical COVID‐19 disease, according to clinical criteria defined by the Chinese Centre for Disease Control and Prevention 8 . Medical co‐morbidities were reported for 359 women 7,9–35 . The most common co‐morbidity was overweight or obesity (n=118, 32.9%), bronchial asthma (n=37, 10.3%), essential hypertension (n=21, 5.8%), and type 2 diabetes mellitus (n=10, 2.8%).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of adverse maternal outcomes was assessed for all 637 pregnant women (Table 1). The rate of intensive care unit (ICU) admission was 9.6% (n=61) (Table 1) and comprised 1 (1.6%) women in the first trimester, 5 (8.2%) women in the second trimester, and 55 (90.2%) women in the third trimester of pregnancy 7,15,18,24–31,42,44,48,53,59,63,66 . Among the 487 women admitted with mild COVID‐19, 9 (1.8%) deteriorated to severe or critical disease necessitating escalation of care to the ICU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the rate of infected women observed in our study is very similar to the prevalence observed in a concomitant survey performed in our area and focusing on blood donors. Speci cally, Valenti et al women with Covid-19 necessitated hospitalization 7 . This rate resulted even higher (69%) in a Spanish cases series of 60 pregnant infected subjects 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Albeit still limited, there is evidence that SARS-Cov-2 can cause life-threatening situations also in pregnancy, even if fatal cases seem rare [5][6][7][8][9] . Severe pneumonia occurs in 5-16% of women 5,8,9 and may require prompt pregnancy termination for improving respiratory assistance.…”
Section: Introductionmentioning
confidence: 99%